2005
DOI: 10.1007/s10162-005-0006-7
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB is Required for Survival of Immature Auditory Hair Cells In Vitro

Abstract: Damage to auditory hair cells in the inner ear as a consequence of aging, disease, acoustic trauma, or exposure to ototoxins underlies most cases of hearing impairment. Because the mammalian ear cannot replace damaged hair cells, loss of hearing is irreversible and progressive throughout life. One of the current goals of inner ear biology is to develop therapeutic strategies to prevent hair cell degeneration. Although important progress has been made in discovering factors that mediate hair cell death, very li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 35 publications
1
41
1
Order By: Relevance
“…Similar to these reports we found a constitutively active form of NF-kappaB in the organ of Corti (OC) of 5-day-old rats. Selective inhibition of NFkappaB in vitro caused massive degeneration of HCs within 24 h of inhibitor application [Nagy et al, 2005]. These data suggest an important role for NF-kappaB in mediating survival of immature auditory HCs.…”
mentioning
confidence: 60%
See 2 more Smart Citations
“…Similar to these reports we found a constitutively active form of NF-kappaB in the organ of Corti (OC) of 5-day-old rats. Selective inhibition of NFkappaB in vitro caused massive degeneration of HCs within 24 h of inhibitor application [Nagy et al, 2005]. These data suggest an important role for NF-kappaB in mediating survival of immature auditory HCs.…”
mentioning
confidence: 60%
“…We have previously shown that this compound and concentration causes HC loss [Nagy et al, 2005]. In the control experiments, an inactive control for the NF-kappaB inhibitor was used (NF-kappaB control, AAVALLPAVLLALLAPVQRDG-QKLMP, Santa Cruz Biotechnology Inc.) at the same final concentration.…”
Section: Inhibition Of Nf-kappab Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…In rat cochlear explants, treatment with an Akt inhibitor promotes gentamicininduced outer hair cell (OHC) death (Chung et al 2006) and diminishes the protective function of dexamethasone against TNFα-initiated apoptosis (Haake et al 2009). Moreover, inhibition of the downstream Akt target NF-κB by aminoglycosides leads to loss of sensory hair cells in explants (Nagy et al 2005(Nagy et al , 2007 and mouse cochleae (Jiang et al 2006). Taken together, this evidence suggests that increasing PI3K/Akt signaling might protect the inner ear from noxious stimuli.…”
Section: Introductionmentioning
confidence: 80%
“…in vitro (Nagy et al, 2005). However, there is little information regarding activation of NFB in the auditory nerve and how NFB activity may affect cochlear function with age and trauma.…”
Section: Discussionmentioning
confidence: 99%